Market position of the Hungarian Football League in international comparison - Kassay, Lili (The Hungarian Journal of Marketing and Management, 2019)
Although the majority of the football clubs run their business based on the local market, the soccer sport itself and its player labour market are global. This structural contradiction causes competitive imbalance among the national championships, and inside the leagues, and resulting in unsustainable business operation for football clubs. The minimum income and expenses levels of the Hungarian clubs’ business plan may be determined based on benchmark research and a soccer consumer survey. Understanding that the position of the Hungarian championship is of the same level as League Two in England, may contribute to an improvement in can improve the strategic decision making.